Structure of long bone fractures of lower limbs at a car injury - Sokol, Viacheslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The most traumatized body region in road traffic accidents is the lower extremities, however, the structure of fractures has not been adequately studied. Objective: to study the structure of long bones fractures of the lower extremities in various nonlethal car injuries. Material and methods. The research material was 116 reports of primary forensic medical examinations of victims with fractures of the femur and/or shin bones resulting from a car injury. When studying the frequency of damage to various areas of the body and the frequency of fractures of long bones of the lower extremities, it was taken into account that 28 victims with polytrauma had multiple injuries, and thus 116 patients revealed 232 injuries of various areas of the body and 138 fractures of long bones of the lower legs. Research methods — retrospective analysis, descriptive statistics. Results. The main contingent of those injuries in the car accident was car drivers (8.5%) and pedestrians (47.3 %) aged 31–50 years. In the general group, the shin (37.9 %), thigh (21.6 %), head (13.8 %) were most injured areas, in the group of car drivers — neck, thigh, chest, shin, in the group of passengers — head, shin and thigh; pedestrians — shin, thigh, head. Due to the predominance of anterior (41.4 %) and anterolateral collisions of a moving car in the group as a whole, in cases of the of pedestrians injuries as well as in cases of in-cabin injuries, the presence of bumper fractures of the lower leg bones, as well as fractures of the femur of various localization, was observed. Conclusions. According to the initial forensic medical examination, a collision of a moving car with a pedestrian (78.4 %) and a collision of moving vehicles (21.6 %) were observed in the structure of non-lethal car accidents. In this case, diaphyseal fractures of the femur (29.8 %) and the shin bones (47.1 %) in the general group and in the group of pedestrians (20.4 and 40.7 %, respectively) predominated. Fractures of the femur of various localization were most often detected also in the in-cabin injuries (50.0 % of the total number of fractures in drivers and passengers).